Low-modulus high-strength near-beta-titanium alloy and preparation method thereof
A low modulus, high strength near-β-titanium alloy is developed via vacuum arc melting and annealing processes, addressing the high modulus issue of titanium alloys, achieving suitable mechanical properties for medical implants.
Patent Information
- Application Number
- CN202411265086.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
Existing titanium alloys used in medical implants have high elastic modulus, leading to stress shielding and implant failure, necessitating the development of a low modulus and high strength near-β-titanium alloy to match the mechanical properties of human bone.
A low modulus, high strength near-β-titanium alloy with a chemical formula of Ti 80-x-y Nb 20 Zr x Sn y Ta z is prepared through non-consumable vacuum arc melting, followed by solution treatment, cold rolling, and stress relief annealing to achieve a reduced elastic modulus and enhanced mechanical properties.
The alloy exhibits an extremely low modulus of 28.9 GPa, tensile strength of 712 MPa, and yield strength of 687 MPa, with XRD showing α″ or ω diffraction peaks, indicating grain refinement and dislocation density increase, making it suitable for biomedical applications.
Smart Images

Figure CN119120987A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal biomaterials, and in particular relates to a low-modulus and high-strength near-β-titanium alloy and a preparation method thereof. Background Art
[0002] Metal biomaterials have the longest history as structural biomaterials, and are mainly used to implant into the human body to repair bones, joints, teeth, and blood vessels. The elastic modulus of the medical stainless steel and Co-Cr alloy used at the beginning is much higher than that of human bones, which can easily cause the "stress shielding" effect and lead to implant failure, and cannot meet the requirements of long-term use. Titanium and titanium alloys have become a research hotspot and important candidate materials in the field of biomedical metal materials due to their comprehensive characteristics such as high specific strength, low elastic modulus, excellent biocompatibility and corrosion resistance.
[0003] For titanium alloys, the key characteristic is to choose a low modulus similar to human bone to avoid stiffness mismatch and stress shielding problems. Therefore, for the study of the characteristics of titanium alloys, starting from the elastic modulus, the development of new excellent titanium alloys is accelerated. Metastable β-Ti or near-β-Ti alloys have a lower elastic modulus when designed, using a flexible combination of non-toxic elements. Therefore, they have long been considered a good choice for biomaterials. Since there is a strong correlation between the elastic modulus of β-Ti alloys and the stability of the β phase, further coupling design of composition and process for near-β-Ti alloys to reduce the modulus is of great significance for the development of medical titanium alloys. Summary of the invention
[0004] The purpose of the present invention is to provide a low modulus and high strength near-β-titanium alloy and a preparation method thereof. The present invention reduces the elastic modulus of the alloy by element doping and cold rolling annealing process, thereby solving the problem of high modulus and low strength of titanium alloy in the prior art.
[0005] The purpose of the present invention is to be achieved through the following technical solutions:
[0006] A low modulus, high strength near-β-titanium alloy with a general chemical formula of Ti 80-x-y Nb 20 Zr x Sn y Ta z , where 2≤x<6, 1≤y<3, 2≤z<5.
[0007] Preferably, the elastic modulus of the low modulus and high strength near-β-titanium alloy is 28.9-52.5 GPa.
[0008] The present invention also provides a method for preparing the low modulus and high strength near-β-titanium alloy as described above, comprising the following steps:
[0009] Using a non-consumable vacuum arc melting method, in a protective atmosphere, the raw material of the low modulus and high strength near-β-titanium alloy is melted, and the molten metal liquid is mixed evenly under magnetic stirring, and then a polycrystalline ingot is obtained after several flipping and melting;
[0010] The polycrystalline ingot is subjected to a solution treatment and then subjected to a water-cooling quenching after the heat preservation is completed;
[0011] The polycrystalline ingot after water cooling and quenching is cold rolled to obtain a cold rolled sheet with a preset thickness.
[0012] Preferably, the raw materials of the low modulus and high strength near-β-titanium alloy are pure Ti metal particles, Nb metal particles, Zr metal particles, Sn metal particles and Ta metal particles with a purity of more than 99.9%.
[0013] Preferably, when the raw material of the low modulus and high strength near-β-titanium alloy is melted in a protective atmosphere by a non-consumable vacuum arc melting method:
[0014] The vacuum degree is 5×10 -3 Pa, the protective atmosphere is argon, the argon protective gas is filled to 0.05MPa, and the smelting current is 350-500A.
[0015] Preferably, the number of flippings is no less than 5 times.
[0016] Preferably, when the polycrystalline ingot is subjected to solution treatment, the solution treatment temperature is 995-1005° C. and the treatment time is 55-65 min.
[0017] Preferably, when the polycrystalline ingot after water cooling and quenching is cold rolled:
[0018] The pressing amount of each pass is controlled to be 0.03-0.05mm, the total cold rolling deformation is 40%-80%, and the final thickness of the cold rolled sheet is 0.6-1.8mm.
[0019] Preferably, the above method of the present invention also includes the following process:
[0020] The cold rolled sheets are subjected to vacuum stress relief annealing and then water quenching.
[0021] Preferably, the temperature of vacuum stress relief annealing is 400-500° C., and the annealing time is 0.5-1 h.
[0022] The present invention has the following beneficial effects:
[0023] The low modulus and high strength near-β-titanium alloy of the present invention is stretched at room temperature and is found to have an extremely low modulus of 28.9 GPa, a tensile strength of 712 MPa, a yield strength of 687 MPa and an elongation of 13%. According to the X-ray diffraction (XRD) spectrum, it can be seen that the sample exhibits obvious α″ or ω diffraction peaks. These results prove that the bcc-β phase with lower stability is accompanied by quenched ω or α″ martensite, so the prepared Ti alloy has an extremely low modulus. The present invention regulates the grain size of the titanium alloy by doping the titanium alloy with four elements with good biocompatibility.
[0024] In the preparation method of the present invention, a plate-like near-β titanium alloy is prepared by simple process methods such as cold rolling and annealing. After the alloy sample is cold-rolled and annealed, the grain refinement and dislocation density increase, resulting in different degrees of increase in the tensile strength and yield strength of the titanium alloy. The combined effects of twin formation, grain refinement and texture evolution lead to a decrease in the elastic modulus of the alloy.
[0025] Furthermore, in the process of stress relief annealing, the modulus of the alloy of the system is reduced as the precipitation of the ω phase and the α phase is suppressed. The Ti-Nb-Zr-Sn-Ta titanium alloy sheet prepared by the process method adopted by the present invention can meet the needs of future biomedicine. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:
[0027] Figure 1 The present invention provides a technical roadmap for the preparation of a low modulus and high strength near-β-titanium alloy.
[0028] Figure 2 It is a plate of a near-β-titanium alloy with low modulus and high strength in the embodiment of the present invention and a tensile specimen used for mechanical testing.
[0029] Figure 3 Room temperature XRD test graphs of the low modulus and high strength near-β-titanium alloy plates prepared in Examples 1 to 5 of the present invention.
[0030] Figure 4 This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 1 of the present invention.
[0031] Figure 5 This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 2 of the present invention.
[0032] Figure 6This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 3 of the present invention.
[0033] Figure 7 This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 4 of the present invention.
[0034] Figure 8 This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 5 of the present invention.
[0035] Fig. 9 This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 6 of the present invention.
[0036] Fig.10 This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 7 of the present invention.
[0037] Fig.11 This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 8 of the present invention.
[0038] Fig.12 This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 9 of the present invention.
[0039] Fig.13 This is the stress-strain curve of the low modulus and high strength near-β-titanium alloy plate prepared in Example 10 of the present invention.
[0040] In the figure, 1 is a cold-rolled plate and 2 is a tensile specimen. DETAILED DESCRIPTION
[0041] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention. In the accompanying drawings:
[0042] like Figure 1 As shown, the present invention takes the preparation of a low modulus and high strength near-β-titanium alloy sheet as an example to illustrate the preparation method and material properties of the alloy of the present invention. Specifically, the preparation method includes the following steps:
[0043] Step 1, according to the material chemical formula Ti 80-x-y Nb 20 Zr x Sn y Ta zThe atomic ratio of the metal elements Ti, Nb, Zr, Sn and Ta in the raw material mixture is 99.9% high-purity Ti metal particles, Nb metal particles, Zr metal particles, Sn metal particles and Ta metal particles are mixed to obtain a metal raw material mixture, wherein 2≤x<6, 1≤y<3, 2≤z<5;
[0044] Step 2: Using non-consumable vacuum arc melting method, fill with argon protective gas to 0.05MPa, under argon protective atmosphere and vacuum degree of 5×10 -3 The metal raw material mixture is melted under the condition of Pa or above, and the molten metal liquid is fully mixed under magnetic stirring, the smelting current is 300-500A, and a polycrystalline ingot is obtained after 5 times of turning over and each time of 1.5min smelting;
[0045] Step 3, subjecting the polycrystalline ingot to a solution heat treatment at 995-1005° C. for 55-65 min and then to a water-cooling quenching treatment;
[0046] Step 4, rolling the polycrystalline ingot at room temperature, repeating the rolling several times in each pass, gradually increasing the reduction amount according to a preset step length, wherein the reduction amount in each pass is 0.03-0.05 mm, and finally controlling the cold rolling deformation amount to 40%-80%, to obtain a cold-rolled sheet with a thickness of 0.6-1.8 mm;
[0047] Step 5, performing mechanical grinding and polishing on the surface of the cold-rolled sheet, and cutting it into tensile specimens of different sizes.
[0048] In addition, the present invention can also subject the tensile specimen obtained in step 5 to a vacuum sealing tube stress relief annealing heat treatment, wherein the annealing is carried out at 400-500° C. for 0.5-1 h and then water-cooled quenching is carried out.
[0049] Embodiment 1:
[0050] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 71 Nb 20 Zr5Sn 1.6 Ta 2.4 , the preparation process comprises the following steps:
[0051] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, Ta metal particle raw materials are weighed according to atomic percentage.
[0052] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes at a working current of 300A and turn them over 5 times, thereby preparing an initial polycrystalline ingot;
[0053] The third step is to perform a solution heat treatment at 995-1005°C for 1 hour and then perform a water cooling quenching treatment on the obtained polycrystalline ingot;
[0054] In the fourth step, the polycrystalline ingot treated in the third step is rolled at room temperature, with each pass pressing down 0.03 mm, and finally the cold rolling deformation is controlled to be 70%, so as to obtain a cold-rolled sheet with a thickness of 1.8 mm.
[0055] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and finally obtain a sheet of high-strength titanium alloy with low modulus and a tensile specimen for mechanical testing such as Figure 2 shown.
[0056] Figure 4 For this embodiment Ti 71 Nb 20 Zr5Sn 1.6 Ta 2.4 The stress-strain curve of the alloy at room temperature shows that the alloy has a low modulus of 28.9 GPa, a tensile strength of 712 MPa, a yield strength of 687 MPa and an elongation of 13%. Figure 3 Ti 71 Nb 20 Zr5Sn 1.6 Ta 2.4 The X-ray diffraction (XRD) patterns of the alloys show that the samples exhibit obvious α″ or ω diffraction peaks. These results prove that the less stable bcc-β phase is accompanied by quenched ω or α″ martensite, which may result in a lower elastic modulus of the Ti alloy.
[0057] Embodiment 2:
[0058] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 71 Nb 20 Zr5Sn 1.6 Ta 2.4 , the preparation process comprises the following steps:
[0059] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, Ta metal particle raw materials are weighed according to atomic percentage.
[0060] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes at a working current of 300A and turn them over 5 times, thereby preparing an initial polycrystalline ingot;
[0061] The third step is to perform a solution heat treatment at 995-1005°C for 1 hour and then perform a water cooling quenching treatment on the obtained polycrystalline ingot;
[0062] In the fourth step, the polycrystalline ingot treated in the third step is rolled at room temperature, with each pass pressing down 0.03 mm, and finally the cold rolling deformation is controlled to be 70%, so as to obtain a cold-rolled sheet with a thickness of 1.8 mm.
[0063] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and then seal it in a vacuum tube for annealing heat treatment at 400°C for 0.5h and then water quenching to finally obtain a sheet of high-strength titanium alloy with low modulus and a tensile specimen for mechanical testing such as Figure 2 shown.
[0064] Figure 5 For this embodiment Ti 71 Nb 20 Zr5Sn 1.6 Ta 2.4 The stress-strain curve of the alloy at room temperature shows that the alloy has a low modulus of 47.8 GPa, a tensile strength of 783 MPa, a yield strength of 762 MPa and an elongation of 14%.
[0065] Embodiment 3:
[0066] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 71.8 Nb 20 Zr 3.2 Sn 2.1 Ta 2.9 , the preparation process comprises the following steps:
[0067] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, and Ta metal particle raw materials are weighed according to atomic percentage.
[0068] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes at a working current of 400A and turn them over 5 times, thereby preparing an initial polycrystalline ingot;
[0069] The third step is to perform a solution heat treatment at 995-1005°C for 1 hour and then perform a water cooling quenching treatment on the obtained polycrystalline ingot;
[0070] In the fourth step, the polycrystalline ingot treated in the third step is rolled at room temperature, with each pass pressing down 0.04 mm, and finally the cold rolling deformation is controlled to be 80%, so as to obtain a cold-rolled sheet with a thickness of 1.2 mm.
[0071] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and finally obtain a sheet of high-strength titanium alloy with low modulus and a tensile specimen for mechanical testing such as Figure 2 shown.
[0072] Figure 6 For this embodiment Ti 71.8 Nb 20 Zr 3.2 Sn 2.1 Ta 2.9 The stress-strain curve of the alloy at room temperature shows that the alloy has a low modulus of 40.5 GPa, a tensile strength of 580 MPa, a yield strength of 565 MPa, and an elongation of 6%. Figure 3 Ti 71.8 Nb 20 Zr 3.2 Sn 2.1 Ta 2.9 The X-ray diffraction (XRD) patterns of the alloys show that the samples exhibit obvious α″ or ω diffraction peaks. These results prove that the less stable bcc-β phase is accompanied by quenched ω or α″ martensite, which may result in a lower elastic modulus of the Ti alloy.
[0073] Embodiment 4:
[0074] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 71.8 Nb 20 Zr 3.2 Sn 2.1 Ta 2.9 , the preparation process comprises the following steps:
[0075] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, and Ta metal particle raw materials are weighed according to atomic percentage.
[0076] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes at a working current of 400A and turn them over 5 times, thereby preparing an initial polycrystalline ingot;
[0077] The third step is to perform a solution heat treatment at 995-1005°C for 55 minutes and then perform a water cooling quenching treatment on the obtained polycrystalline ingot;
[0078] In the fourth step, the polycrystalline ingot processed in the third step is rolled at room temperature, with each pass pressing down 0.04 mm, and finally the cold rolling deformation is controlled to be 80%, so as to obtain a cold-rolled sheet with a thickness of 1.2 mm.
[0079] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and then seal it in a vacuum tube for annealing heat treatment at 400℃ for 1h and then water quenching, finally obtaining a sheet of high-strength titanium alloy with low modulus and a tensile specimen for mechanical testing such as Figure 2 shown.
[0080] Figure 7 For this embodiment Ti 71.8 Nb 20 Zr 3.2 Sn 2.1 Ta 2.9 The stress-strain curve of the alloy at room temperature shows that the alloy has a low modulus of 51.2 GPa, a tensile strength of 650 MPa, a yield strength of 625 MPa, and an elongation of 6%.
[0081] Embodiment 5:
[0082] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 70.7 Nb 20 Zr 4.6 Sn 1.9 Ta 2.8 , the preparation process comprises the following steps:
[0083] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, Ta metal particle raw materials are weighed according to atomic percentage.
[0084] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes at a working current of 500A and turn them over 5 times, thereby preparing an initial polycrystalline ingot;
[0085] The third step is to perform a solution heat treatment at 995-1005°C for 55 minutes on the polycrystalline ingot after the third step, and then perform a water cooling quenching treatment;
[0086] In the fourth step, the obtained polycrystalline ingot is rolled at room temperature, with each pass pressing down 0.03 mm, and finally the cold rolling deformation is controlled to be 40%, so as to obtain a cold-rolled sheet with a thickness of 0.8 mm.
[0087] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and finally obtain a sheet of high-strength titanium alloy with low modulus and a tensile specimen for mechanical testing such as Figure 2 shown.
[0088] Figure 8 For this embodiment Ti 70.7 Nb20 Zr4.6Sn 1.9 Ta 2.8 The stress-strain curve of the alloy at room temperature shows that the alloy has a low modulus of 43.3 Gpa, a tensile strength of 710 MPa, a yield strength of 659 MPa, and an elongation of 8%. Figure 3 Ti 70.7 Nb 20 Zr4.6Sn 1.9 Ta 2.8 The X-ray diffraction (XRD) patterns of the alloys show that the samples exhibit obvious α″ or ω diffraction peaks. These results prove that the less stable bcc-β phase is accompanied by quenched ω or α″ martensite, which may result in a lower elastic modulus of the Ti alloy.
[0089] Embodiment 6:
[0090] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 70.7 Nb 20 Zr 4.6 Sn 1.9 Ta 2.8 , the preparation process comprises the following steps:
[0091] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, Ta metal particle raw materials are weighed according to atomic percentage.
[0092] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes at a working current of 450A and turn them over 5 times, thereby preparing an initial polycrystalline ingot;
[0093] The third step is to perform a solution heat treatment at 995-1005°C for 65 minutes on the polycrystalline ingot after the third step, and then perform a water cooling quenching treatment;
[0094] In the fourth step, the obtained polycrystalline ingot is rolled at room temperature, with each pass pressing down 0.03 mm, and finally the cold rolling deformation is controlled to be 40%, so as to obtain a cold-rolled sheet with a thickness of 0.8 mm.
[0095] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and store it in a vacuum tube for annealing heat treatment at 400°C for 0.5h and then water quenching, finally obtaining a sheet of high-strength titanium alloy with low modulus and a tensile specimen for mechanical testing such as Figure 2 shown.
[0096] Fig. 9 For this embodiment Ti 70.7 Nb 20Zr4.6Sn 1.9 Ta 2.8 The stress-strain curve of the alloy at room temperature. The curve shows that the alloy has a low modulus of 51.5Gpa, a tensile strength of 691Mpa, a yield strength of 676Mpa, and an elongation of 6%.
[0097] Embodiment 7:
[0098] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 70.6 Nb 20 Zr 2.5 Sn 2.5 Ta 4.4 , the preparation process comprises the following steps:
[0099] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, Ta metal particle raw materials are weighed according to atomic percentage.
[0100] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes at a working current of 350A and turn them over 5 times, thereby preparing an initial ingot;
[0101] The third step is to perform a solution heat treatment at 995-1005°C for 65 min and then perform a water cooling quenching treatment on the obtained ingot;
[0102] In the fourth step, the polycrystalline ingot processed in the third step is rolled at room temperature, with each pass pressing down 0.03 mm, and finally the cold rolling deformation is controlled to be 40%, so as to obtain a cold-rolled sheet with a thickness of 0.6 mm.
[0103] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and finally obtain high-strength titanium alloy with low modulus such as Figure 2 shown.
[0104] Fig.10 For this embodiment Ti 70.6 Nb 20 Zr 2.5 Sn 2.5 Ta 4.4 The stress-strain curve of the alloy at room temperature shows that the alloy has a low modulus of 49.8 Gpa, a tensile strength of 790 MPa, a yield strength of 757 MPa, and an elongation of 8%. Figure 3 Ti 70.6 Nb 20 Zr 2.5 Sn 2.5 Ta 4.4The X-ray diffraction (XRD) patterns of the alloys show that the samples exhibit obvious α″ or ω diffraction peaks. These results prove that the less stable bcc-β phase is accompanied by quenched ω or α″ martensite, which may result in a lower elastic modulus of the Ti alloy.
[0105] Embodiment 8:
[0106] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 70.6 Nb 20 Zr 2.5 Sn 2.5 Ta 4.4 , the preparation process comprises the following steps:
[0107] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, Ta metal particle raw materials are weighed according to atomic percentage.
[0108] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes at a working current of 350A and turn them over 5 times, thereby preparing an initial ingot;
[0109] The third step is to perform a solution heat treatment at 995-1005°C for 1 hour and then perform a water cooling quenching treatment;
[0110] In the fourth step, the polycrystalline ingot processed in the third step is rolled at room temperature, with each pass pressing down 0.03 mm, and finally the cold rolling deformation is controlled to be 40%, so as to obtain a cold-rolled sheet with a thickness of 0.6 mm.
[0111] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and store it in a vacuum tube for annealing heat treatment at 500°C for 40 minutes and then water quenching, finally obtaining a high-strength titanium alloy with low modulus such as Figure 2 shown.
[0112] Fig.11 For this embodiment Ti 70.6 Nb 20 Zr 2.5 Sn 2.5 Ta 4.4 The stress-strain curve of the alloy at room temperature shows that the alloy has a low modulus of 52.5 Gpa, a tensile strength of 708 MPa, a yield strength of 674 MPa and an elongation of 9%.
[0113] Embodiment 9:
[0114] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 67.9 Nb20 Zr 5.5 Sn 2.3 Ta 4.3 , the preparation process comprises the following steps:
[0115] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, and Ta metal particle raw materials are weighed according to atomic percentage.
[0116] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes and turn them over 5 times at a working current of 400A, thereby preparing an initial ingot;
[0117] The third step is to perform a solution heat treatment at 995-1005°C for 1 hour and then perform a water cooling quenching treatment;
[0118] In the fourth step, the polycrystalline ingot processed in the third step is rolled at room temperature, with each pass pressing down 0.05 mm, and finally the cold rolling deformation is controlled to be 80%, so as to obtain a cold-rolled sheet with a thickness of 1.2 mm.
[0119] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and finally obtain high-strength titanium alloy with low modulus such as Figure 2 shown.
[0120] Fig.12 For this embodiment Ti 67.9 Nb 20 Zr 5.5 Sn 2.3 Ta 4.3 The stress-strain curve of the alloy at room temperature shows that the alloy has a low modulus of 48.7 Gpa, a tensile strength of 640 MPa, a yield strength of 629 MPa, and an elongation of 6%. Figure 3 Ti 67.9 Nb 20 Zr 5.5 Sn 2.3 Ta 4.3 The X-ray diffraction (XRD) patterns of the alloys show that the samples exhibit obvious α″ or ω diffraction peaks. These results prove that the less stable bcc-β phase is accompanied by quenched ω or α″ martensite, which may result in a lower elastic modulus of the Ti alloy.
[0121] Embodiment 10:
[0122] The composition of the low modulus and high strength near-β-titanium alloy sheet in this embodiment is Ti 67.9 Nb 20 Zr 5.5 Sn 2.3Ta 4.3 , the preparation process comprises the following steps:
[0123] In the first step, 99.9% high purity Ti, Nb, Zr, Sn, and Ta metal particle raw materials are weighed according to atomic percentage.
[0124] In the second step, the metal raw materials are mixed evenly, placed in a Cu crucible with a water cooling cycle, and a non-consumable vacuum arc melting method is used to melt the raw materials for a single time of 1.5 minutes and turn them over 5 times at a working current of 400A, thereby preparing an initial ingot;
[0125] The third step is to perform a solution heat treatment at 995-1005°C for 1 hour and then perform a water cooling quenching treatment;
[0126] In the fourth step, the polycrystalline ingot processed in the third step is rolled at room temperature, with each pass pressing down 0.05 mm, and finally the cold rolling deformation is controlled to be 80%, so as to obtain a cold-rolled sheet with a thickness of 1.2 mm.
[0127] The fifth step is to perform mechanical grinding and polishing on the surface of the cold-rolled sheet, and then process it into samples of different sizes by electric spark cutting, and store them in a vacuum tube for annealing heat treatment at 450°C for 0.5h and then water quenching, finally obtaining a high-strength titanium alloy with low modulus such as Figure 2 shown.
[0128] Fig.13 For this embodiment Ti 67.9 Nb 20 Zr 5.5 Sn 2.3 Ta 4.3 The stress-strain curve of the alloy at room temperature shows that the alloy has a low modulus of 38.4 Gpa, a tensile strength of 675 MPa, a yield strength of 647 MPa, and an elongation of 10%.
[0129] Table 1 shows the mechanical properties comparison between the Ti-Nb-Zr-Sn-Ta series titanium alloy (i.e., low modulus and high strength near-β-titanium alloy) prepared by the method of the present invention and the existing titanium alloy.
[0130] Table 1
[0131]
[0132]
[0133] As can be seen from Table 1, compared with other existing Ti alloy blocks or plates, the modulus of the Ti-Nb-Mo-Zr-Sn-Ta alloy plate prepared by the method of the present invention has been greatly reduced while maintaining a large yield strength. At the same time, compared with the TiNbZr alloy with similar performance obtained by genetic algorithm design, the alloy Mo and Ta content prepared by this method is lower, so the smelting difficulty of the raw materials is lower; in addition, compared with the Ti2448 alloy, the preparation process of this method is relatively simple, and the obtained alloy plate has a wider process adjustment range, stronger stability, and is more suitable for industrial large-scale production and application. It can be seen from the results of the above embodiments that the present invention achieves an extremely low modulus (28.9GPa) with strong repeatability. This shows that our candidate alloy has the potential to be used as an implant material. In general, the low modulus Ti-Nb-Zr-Sn-Ta alloy plate prepared by the method of the present invention has a high commercial application potential.
[0134] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A low modulus and high strength near-β-titanium alloy, characterized in that: Its chemical formula is Ti 80-x-y Nb 20 Zr x Sn y Ta z , where 2≤x<6, 1≤y<3, 2≤z<5.
2. A low modulus and high strength near-β-titanium alloy according to claim 1, characterized in that: The elastic modulus of the low modulus and high strength near-β-titanium alloy is 28.9-52.5 GPa.
3. The method for preparing the low modulus and high strength near-β-titanium alloy according to claim 1 or 2, characterized in that: The process includes the following: Using a non-consumable vacuum arc melting method, in a protective atmosphere, the raw material of the low modulus and high strength near-β-titanium alloy is melted, and the molten metal liquid is mixed evenly under magnetic stirring, and then a polycrystalline ingot is obtained after several flipping and melting; The polycrystalline ingot is subjected to solution treatment, and water-cooled quenching is performed after the heat preservation is completed; The polycrystalline ingot after water cooling and quenching is cold rolled to obtain a cold rolled sheet with a preset thickness.
4. The method for preparing a low modulus and high strength near-β-titanium alloy according to claim 3, characterized in that: The raw materials of the low modulus and high strength near-β-titanium alloy are pure Ti metal particles, Nb metal particles, Zr metal particles, Sn metal particles and Ta metal particles with a purity of more than 99.9%.
5. The method for preparing a low modulus and high strength near-β-titanium alloy according to claim 3, characterized in that: When the raw material of the low modulus and high strength near-β-titanium alloy is melted in a protective atmosphere by a non-consumable vacuum arc melting method: The vacuum degree is 5×10 -3 Pa, the protective atmosphere is argon, the argon protective gas is filled to 0.05MPa, and the smelting current is 350-500A.
6. The method for preparing a low modulus and high strength near-β-titanium alloy according to claim 3, characterized in that: Turn over at least 5 times.
7. The method for preparing a low modulus and high strength near-β-titanium alloy according to claim 3, characterized in that: When the polycrystalline ingot is subjected to solution treatment, the solution treatment temperature is 995-1005° C. and the treatment time is 55-65 min.
8. The method for preparing a low modulus and high strength near-β-titanium alloy according to claim 3, characterized in that: When cold rolling a polycrystalline ingot after water cooling and quenching: The pressing amount of each pass is controlled to be 0.03-0.05mm, the total cold rolling deformation is 40%-80%, and the final thickness of the cold rolled plate is 0.6-1.8mm.
9. The method for preparing a low modulus and high strength near-β-titanium alloy according to claim 3, characterized in that: It also includes the following processes: The cold rolled sheets are subjected to vacuum stress relief annealing and then water quenching.
10. The method for preparing a low modulus and high strength near-β-titanium alloy according to claim 9, characterized in that: The temperature of vacuum stress relief annealing is 400-500°C, and the annealing time is 0.5-1h.
